Risk factors associated with nocturia in patients with obstructive sleep apnea syndrome. Issue 3 (27th October 2020) - Deger, Mutlu; Surmelioglu, Ozgur; Kuleci, Sedat; Izol, Volkan; Akdogan, Nebil; Onan, Elvan; Tanrisever, Ilda; Aridogan, Ibrahim Atilla
Abstract: Aim: To evaluate the risk factors associated with nocturia in patients with obstructive sleep apnea syndrome (OSAS). Materials and Methods: Patients aged over 18 years who had been diagnosed with OSAS using polysomnography (PSG) from January to December 2019 were evaluated. The number of nocturia episodes had been assessed in a 3‐day bladder diary. We analysed the age, sex, body mass index (BMI) score, apnea‐hypopn ea index (AHI) score and severity, hypertension, diabetes mellitus, smoking and heart diseases in all patients. Results: A total of 124 patients with a mean age of 49.9 ± 11.6 years (range: 25‐81 years) were included in the study. Ninety‐two (75.8%) patients had nocturia. The mean number of nocturia episodes of patients with nocturia was 2.4 ± 1.3. To determine factors affecting the risk of nocturia, the logistic regression analysis was performed. Patient age and BMI scores were found as the most effective risk factors determining nocturia ( P < .05). The odds of patient age were 1.06 (odds ratio: 1.12; 95% confidence interval: 1.01‐1.11; P = .010) times higher for patients with nocturia. Every 1‐unit increase in the BMI score increased the risk of nocturia 1.12 times. In the study period, 48 patients with nocturia had undergone the continuous positive airway pressure (CPAP) therapy or surgical treatment. The mean number of nocturia episodes of these patients was 2.3 ± 1.4 before treatment and 1.7 ± 2.2 after treatment, showing a significant decrease ( P = .032). Although the total daily urine volume increased significantly with the treatment, the total night‐time urine volume decreased significantly at night ( P = .016 and P = .024, respectively). Conclusion: The age and BMI score were the risk factors associated with nocturia in patients with OSAS.